A QUESTIONNAIRE CONTAINING A CALL COMPONENT FOR STUDENTS OF ESP – PILOT STUDY RESULTS - Olejarczuk , Edyta (Neofilolog, 2020)
As Arnó-Macià (2012: 89) points out: “Within the integration of technology into language education, special attention needs to be paid to languages for specific purposes (LSP) (…)”. Although a broad range of technologies may support the process of language learning, this paper investigates those technologies which are connected with the computer and Internet use in order to learn a foreign language. A term used to refer to the above-mentioned issue is Computer-Assisted Language Learning (CALL). The paper presents results of a pilot study conducted of students of English for Specific Purposes (ESP) using a questionnaire containing a CALL component. This data collection instrument was especially designed for the purpose of the research. The main aim of the present article is to consider how to measure participants’ competences, attitudes and skills in the area of ICT (Information and Communication Technology).